2009
DOI: 10.1038/onc.2009.369
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a major colon cancer susceptibility locus (Ccs3) on mouse chromosome 3

Abstract: Treatment of mice with the carcinogen azoxymethane (AOM) induces a number of lesions in the colon, including hyperplastic lesions, as well adenomas and carcinomas in situ. Inbred strains of mice show different responses to AOM-induced carcinogenesis. A/J mice are highly susceptible and develop a greater number of hyperplastic lesions and tumors (15-70 tumors per mouse) than resistant C57BL/6J mice (0-6 tumors per mouse). Susceptibility to AOM-induced tumors segregates as a co-dominant trait in (A Â B6)F1 hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…The presence of such discordant strains in both sets of RCS suggests the possibility that the restrictiveness/permissiveness trait is under simple genetic control, and that transfer of a single congenic fragments onto the opposite strain background strongly influences the phenotype of the recipient strain. Such a situation would be similar to the segregation of the Ccs3 (colorectal cancer) [28], Ity (susceptibility to Salmonella ) [29] and Lgn1 loci (susceptibility to Legionella ) [19] we previously reported in these strains.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of such discordant strains in both sets of RCS suggests the possibility that the restrictiveness/permissiveness trait is under simple genetic control, and that transfer of a single congenic fragments onto the opposite strain background strongly influences the phenotype of the recipient strain. Such a situation would be similar to the segregation of the Ccs3 (colorectal cancer) [28], Ity (susceptibility to Salmonella ) [29] and Lgn1 loci (susceptibility to Legionella ) [19] we previously reported in these strains.…”
Section: Resultssupporting
confidence: 83%
“…The panel of 34 reciprocal AcB/BcA RCS has been used to map major monogenic traits [19], [28] or to facilitate identification of multiple loci involved in complex trait diseases [26], [27]. This approach is based on the premise that unique small congenic fragments derived from the donor strain are fixed and delineated for each strain, which may allow for detection of causative haplotype by the sole study of the strain distribution pattern in relation to the phenotype of interest [19].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, no differences were detected in the frequency of tumors in the small intestine (SI) (Figure S1B), where tumor development in Apc Min/+ mice does not depend on a second genetic event. We next investigated the role of FcRn in the development of CRC induced by the chronic exposure of a chemical carcinogen, azoxymethane (AOM), which, upon repeated administration, drives the development of colorectal malignancies (Meunier et al, 2009). We observed that Fcgrt −/− mice subjected to a standard regimen of AOM administration developed significantly more abundant and larger tumors (Figures 1B and S1C) than did WT littermates.…”
Section: Resultsmentioning
confidence: 99%
“…All procedures were approved by the Harvard Medical Area Standing Committee on Animals. AOM, AOM/DSS, Apc min/+ and lung metastasis tumor models were performed using previously described protocols (LeibundGut-Landmann et al, 2008; Meunier et al, 2009; Wirtz et al, 2007) and are described fully in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…After sacrificing the mice, entire colons were removed, rinsed with PBS, opened longitudinally and fixed flat on strips of 4% paraformaldehyde-soaked Whatman filter paper. Colons were assessed in a blinded fashion under a stereo-dissecting microscope as previously described [63]. Tumors were measured using a clear transparency of 1 mm 2 graph paper, and the total surface area was determined based on the total number of squares overlaying the tumor, as described [64].…”
Section: Methodsmentioning
confidence: 99%